The Urgency of the Diplomatic Role of the Indonesian Navy in Supporting Security Stability in the Indo-Pacific Region - Mayang Agneztia Parasasti; I Wayan Warka; Agus Adriyanto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Over the past few years, the intensity of use of the term "Indo-Pacific" has been increasingly encountered in various strategic discussions. Currently, the Indo-Pacific is an important area that reflects global geopolitics in the 21st century because it is the most strategic international trade and shipping route. In addition to its strategic location, the Indo-Pacific also causes various threat dynamics, especially due to the presence of various large countries in the region that are trying to exercise their hegemony. The dynamics of threats that are often encountered in this region include issues of the South China Sea, US-China rivalry, maritime disputes, and maritime security. In the midst of the increasingly complex dynamics of threats in the Indo-Pacific region, the Indonesian Navy has the duty and support for creating regional security through the role of Navy diplomacy. This article uses a qualitative method with a case study approach. The several theories used are regional security complexity theory, threat theory, and naval diplomacy. There are three important points elaborated in the discussion including: The security complexity and dynamics of threats in the Indo-Pacific region, Regional cooperation to achieve regional stability, and Implementation of the Indonesian Navy's diplomatic role in the region.